Comparative Study of Three Different BACTEC Culture Media for the Detection of Bacteremia in Ambulatory and Hospitalized Children - Deirdre L Church; H Dele Davies; G Cadrain; Cynthia L Trevenen (Canadian Journal of Infectious Diseases)
To compare the yield of two aerobic and an anaerobic BACTEC blood culture media in detecting bacteremia in ambulatory and hospitalized care settings at a children’s hospital, a prospective cohort study was completed. Over an 18-month period, equal blood volumes (minimum of 1 mL/bottle) were inoculated into a three-bottle culture set including aerobic BACTEC NR 6A, aerobic BACTEC PEDS Plus and anaerobic NR 7A broths. Chart reviews were completed on all children with bacteremia to determine whether the isolate was clinically significant based on predefined criteria. Among 5328 evaluable blood culture sets, 323 clinically significant organisms (110 from ambulatory and 213 from hospitalized children) were isolated. Most Streptococcus pneumoniae, Haemophilus species, and Neisseria or Moraxella species were recovered from children attending the emergency department or out-patient clinics. Important isolates in hospitalized children included most of the staphylococci and Enterobacteriaceae, and all group D enterococci, Gram-negative nonfermentative bacilli and all Candida species. Overall, significantly more isolates were detected only in the anaerobic bottle from ambulatory children (P<0.0001), including 13 of 54 (24%) patients with S pneumoniae bacteremias presenting to the emergency department. This study indicated that different BACTEC blood culture media combinations are needed in ambulatory and hospitalized pediatric care settings to ensure the optimal recovery of all types of isolates. Whereas aerobic blood culture bottles are adequate for detection of bacteremia in hospitalized children, the common occurrence of fastidious organisms mandates the need for a combined aerobic/anaerobic culture set in ambulatory pediatric care settings.